The Relationship Between Leadership and Organizational Commitment Towards Employee Morale - I Komang Oka Permadi; Ida Ayu Sintha Agustina (Ekonomis: Journal of Economics and Business, 2022)
The success or failure of an organization in achieving a goal is largely determined by human resources. Although other factors are also important, such as capital and equipment, in the end it is humans who will act as managers and implementers, so that organizational goals can be achieved properly. The purpose of this study is to explain the relationship between leadership and organizational commitment to work morale and to confirm the variables of these relationships and also the effect of the influence of these variables. This study uses a non-probability sampling method with a saturated sampling technique (census), with a sample of 72 people from the entire population. Spearman rank correlation analysis, determination, t test, and test were used as data analysis techniques, and SPSS Version 22.0 was used to test the data obtained in this study. The results showed that leadership and organizational commitment had a positive and significant effect on employee morale, either partially or simultaneously.